TRANSFORMASI PEMBELAJARAN UNTUK MENCIPTAKAN PENGALAMAN PENGGUNAAN TIK MELALUI BLENDED LEARNING - Rahmi, Ulfia; Azrul, Azrul (Prodi Teknologi Pendidikan, 2019)
This study aims to analyze the learning transformation process of future educators and education personnel through the application of blended learning as an effort to optimize the implementation of the ICT-based curriculum. The problem that occurs is the lack of relevance of the learning activities of prospective educators and education staff in higher education to current and future field conditions and needs. This research was conducted on 32 students who were enrolled in the Learning and Learning Theory course. Data were collected through: 1) observation of learning activities and assignments at each meeting, both in person and virtual, and 2) interviews with students who attended the lecture. Then the data were analyzed descriptively qualitatively. The results show that there is a transformation of learning for prospective educators and education staff through blended learning. Blended learning creates high learning interactivity so that prospective educators and education staff have learning experiences, especially using ICT as long as students are given wide opportunities to be actively involved.Penelitian ini bertujuan untuk menganalisis proses transformasi pembelajaran calon pendidik dan tenaga kependidikan masa depan melalui penerapan blended learning sebagai upaya untuk mengoptimalkan implementasi kurikulum berbasis ICT. Masalah yang terjadi adalah kurang relevannya kegiatan pembelajaran calon pendidik dan tenaga kependidikan di perguruan tinggi dengan keadaan dan kebutuhan lapangan saat ini dan masa depan. Penelitian ini dilakukan terhadap 32 mahasiswa yang terdaftar pada mata kuliah Teori Belajar dan Pembelajaran. Data dikumpulkan melalui: 1) observasi terhadap kegiatan pembelajaran dan tugas-tugas setiap pertemuan baik langsung maupun virtual, dan 2) wawancara dengan mahasiswa yang mengikuti perkuliahan tersebut. Kemudian data tersebut dianalisis secara kualiitatif deskriptif. Hasilnya menunjukkan bahwa terjadi transformasi pembelajaran bagi calon tenaga pendidik dan kependidikan melalui blended learning. Blended learning menciptakan interaktivitas pembelajaran yang tinggi sehingga calon tenaga pendidik dan kependidikan memiliki pengalaman belajar terutama menggunakan ICT selama mahasiswa diberikan kesempatan yang luas untuk terlibat secara aktif.